Insulin Signaling Impairment in the Brain as a Risk Factor in Alzheimer’s Disease - Hölscher, Christian (Frontiers in Aging Neuroscience, 2019)
Type 2 diabetes is a risk factor for developing Alzheimer’s disease (AD). The underlying mechanism that links up the two conditions seems to be the de-sensitisation of insulin signalling. In patients with AD, insulin signalling was found to be de-sensitised in the brain, even if they did not have diabetes. Insulin is an important growth factor that regulates cell growth, energy utilisation, mitochondrial function and replacement, autophagy, oxidative stress management, synaptic plasticity and cognitive function. Insulin desensitisation therefore can enhance the risk of developing neurological disorders in later life. Other risk factors such as high blood pressure or brain injury also enhance the likelihood of developing AD. All of those risk factors have one thing in common – they induce a chronic inflammation response in the brain. Pro-inflammatory cytokines block growth factor signalling and enhance oxidative stress. The underlying molecular processes for this are described in the review. Treatments to re-sensitise insulin signalling in the brain are also described, such as nasal insulin tests in AD patients, or treatments with re-sensitising hormones such as leptin, ghrelin, glucagon-like peptide 1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP). First clinical trials show promising results and are a proof of concept that utilising such treatments is valid.